Using geography to help teach history: dual-encoding history lesson plans - Tabor, Lisa Kay (Kansas State University, 2011)
Analysis of polling documents indicates how little most Americans know about the world. Geography education is the key to offsetting geographic illiteracy. Fortunately programs designed to improve K-12 geography education are growing in number and strength. How can we teach more and better geography within the school system? Given the dominant role of history in the K-12 social studies curriculum, use of the psychological theory of dual-encoding to integrate geography and history lesson planning is one approach to bring more geography into the classroom. As part of Kansas Geographic Alliance programmatic activity, Kansas history and geography standards, with emphasis on the tested standards, were assessed to identify candidate themes for development of dual-encoded educational units and associated lesson plans. Three workshops were delivered to share these dual-encoded units and lesson plans. The workshops were for education faculty, teachers getting in-service professional development, and for a group of pre-service teachers in a social studies methods class. Attendees at the workshops provided assessment and feedback of the material. Based on informal comments and written responses from the workshop attendees, it is concluded that dual-encoding will enable considerable progress in geography education. Not only will the knowledge provided demonstrate the impact and significance of geography to history teachers and their students, but dual-encoded lessons will advance teacher content and pedagogical knowledge, and most importantly students will learn both geography and history better.
Keywords: geography education; dual-encoding; lesson planning; history; Education, Curriculum and Instruction (0727); Education, Sciences (0714); Education, Social Sciences (0534); Education, Teacher Training (0530); Geography (0366)